Differentiate the function. g(x)=3x^(-3)(x^4 -3x^3 +15x-4)

Awainaideannagi 2022-07-28 Answered
Differentiate the function.
g ( x ) = 3 x 3 ( x 4 3 x 3 + 15 x 4 )
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Answers (2)

Anaya Gregory
Answered 2022-07-29 Author has 14 answers
distribute ( 3 x 3 )   t o   x 4 3 x 3 + 15 x 4
so that simplifies to 3 x 9 + 45 x 2 12 x 3
now differentiate the above funt
g ( x ) = 3 x 9 + 45 x 2 12 x 3
g ( x ) = 3 0 90 x 36 x 2
g ( x ) = 3 90 x 36 x 2
Not exactly what you’re looking for?
Ask My Question
Donna Flynn
Answered 2022-07-30 Author has 3 answers
g ( x ) = 3 x 3 ( x 4 3 x 3 + 15 x 4 )
First multiply g ( x ) = 3 x 3 ( x 4 3 x 3 + 15 x 4 ) = 3 x 9 + 45 x 2 12 x 3
Now differentiate using the power rule which is d d x [ x n ] = n x n 1
So, g ( x ) = 3 90 x 3 + 36 x 4   o r   g ( x ) = 3 90 x 3 + 36 x 4
Not exactly what you’re looking for?
Ask My Question

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

You might be interested in

New questions